In situ Studies of Electrochemical Energy Conversion and Storage Technologies: From Materials, Intermediates, and Products to Surroundings - Chen, Xing; Sun, Yu‑Lin; Lin, Xiu‑Mei; Dong, Jin‑Chao; Li, Jian‑Feng (Nano-Micro Letters, 2026)
Escalating global energy demands and climate urgency necessitate advanced electrochemical energy conversion and storage technologies (EECSTs) like electrocatalysis and rechargeable batteries. Improving their performance relies on elucidating reaction mechanisms and structure-performance relationships via in situ studies. This review summarizes recent in situ studies of EECSTs through a variety of advanced characterization techniques aiming at mapping reaction pathways for the rational design of overall high-performance reaction systems. We outline the principles, capabilities, advantages, and limitations of various in situ techniques. Their applications in in situ studies of fuel cells, water/CO2 electrolysis, and lithium batteries are highlighted with representative examples. These studies enable dynamic tracking of chemical and structural evolution of overall reaction systems, including materials, intermediates, products, and surroundings during operation, providing insights critical to rational system design. Future advancements will involve integrating multimodal in situ/operando approaches with artificial intelligence to enable real-time monitoring at practical scales. Such integration promises precise mechanistic insights and robust structure-performance correlations, ultimately accelerating the development of high-performance EECSTs aligned with sustainability and market requirements. Highlights: 1 An overview of the principles, capabilities, advantages, and limitations of various advanced in situ characterization techniques is provided. 2 In situ studies of fuel cells, water electrolysis, CO2 reduction reaction, and lithium batteries are reviewed across multiple scales, from materials to surroundings. 3 Challenges and prospects of in situ studies of electrochemical energy conversion and storage technologies are proposed.